KONTRIBUSI KOORDINASI MATA TANGAN TERHADAP KETEPATAN SERVIS ATAS PERMAINAN BOLA VOLI MINI PADA SISWA SDN 036/VI RANTAU PANJANG III KECAMATAN TABIR - Iswanto, Kiki; Maulana Putra, Ikhsan (LPPM UNIVERSITAS MUHAMMADIYAH MUARA BUNGO, 2024)
Abstract In this research, a problem was found based on the researcher's direct observation, namely that the service made was often not on target when hitting so that the ball's path was not directed and did not enter the opponent's area correctly. In this study, the aim was to find out how much hand-eye coordination contributes to the accuracy of mini volleyball serves among students at SDN 036/VI Rantau Panjang III, Tabir District. This research is correlational research. In this study, the population was all students in grades V and VI, totaling 46 students. Meanwhile, the sample collection technique was carried out using the Strafied Random Sampling Technique, where in this study there were 20 students. Data analysis was carried out using Product Moment Correlation using a correlation test. In this research, the results show that there is a contribution between hand eye coordination to the accuracy of the bottom serve in the mini volleyball game among students at SDN 036/VI Rantau Panjang III, Tabir District with a percentage of 52.88%. Keywords: eye hand coordination, top service accuracy, Students